Assessment of adherence to asthma controllers in children and adolescents. Issue 8 (22nd July 2020) - Marckmann, Mads; Hermansen, Mette N.; Hansen, Kirsten S.; Chawes, Bo L.
Abstract: Background: Low adherence to asthma controllers is known to increase the risk of uncontrolled disease and poor health outcomes. We aimed to study risk factors of long‐term adherence to preventive medications in children and adolescents with asthma. Methods: Adherence was assessed during a two‐year period in 155 children with asthma followed in a tertiary pediatric asthma outpatient clinic using percentage of days covered (PDC) based on physician prescriptions and pharmacy claims data. The risk factor analysis included age, sex, ethnicity, BMI, atopic comorbidity, spirometry incentives, and fractional exhaled nitric oxide (FeNO). Results: Ninety‐five children, 50 (53%) males, mean age of 16.3 years (SD, 2.36), received at least one prescription for asthma controllers in the study period. Fifty‐two (54%) children were classified as non‐adherent with a PDC cutoff at 80%. Adherence was negatively associated with age: adherence ratio (AR) 0.84 (95% CI, 0.73‐0.95), P  = .008; forced expiratory volume in 1 second (FEV1): AR per L 0.6 (0.91‐1.0), P  = .03; unfilled inhaled beta‐2‐agonist prescription: AR 0.45 (0.23‐0.89), P  = .02; and FeNO level: AR per ppb 0.98 (0.97‐0.99), P  = .03, where age and FeNO retained significance in multivariate analysis. Type and number of asthma controllers were not associated with adherence. Conclusions: This study shows low adherence to preventive medication among half of the children with asthma, which is associated with increasing age and FeNO level. Therefore, an extra effort should be directed toward teenagers transitioning from pediatric to adult medicine and toward inhaled corticosteroid‐treated patients with elevated FeNO to increase their adherence to asthma controllers.